Heterokaryon formation in Ascobolus immersus is not affected by mating type - Bernard C. Lamb; Wei Mun Chan (Fungal Genetics Reports, 1996)
The ability of Ascobolus immersus to form vegetative heterokaryons between strains of the same mating type and between strains of opposite mating type was tested using auxotrophs and morphological markers. Heterokaryon formation, confirmed by hyphal-tip culture, was not affected by mating type; in several other filamentous fungi, vegetative heterokaryons only form between strains of the same mating type.